A new berry-fruited species of Begonia (Begoniaceae) from Xizang (Tibet) in China - Chen, Wen-Hong; Guo, Shi-Wei; Radbouchoom, Sirilak; Dong, Wen-Ke; Wang, Zhong-Xuan; Xi, Hui-Hui; Shui, Yu-Min (Phytotaxa, 2019)
Based on field surveys in Southeastern Xizang and detailed examination of specimens in several herbaria, a new species with berry-like fruits, Begonia pseudoheydei, is herein confirmed and described. Its relationship with the similar species Begonia longifolia from Asia, and its morphological homoplasy with the species Begonia heydei from Central America, are discussed.